FAKTOR FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN SEKTOR PROPERTY, REAL ESTATE DAN BUILDING CONSTRUCTION - Gracia E. Simanjuntak; Dimita Hemalli Premasari Purba (Universitas Methodist Indonesia, 2022)
The aim of this research was examine and analyze the effect ofownership structure, capital structureand company size on the corporate financial performance.The corporate financial performance in this study is measured using Return on Asset (ROA) the ownership structureas measured by managerial ownership, capital structureas measured by the Debt Equity Ratio (DER) and company sizeas measured by the total assets. The sample used was 20 companies from a population of 54 property, real estate and building construction companies that listed in Indonesia Stock Exchange 2015-2019 and obtained a total of 100 observations for the period 2015-2019. The sample is determined using the purposive sampling method. This study uses multiple regression analysis and is processed using SPSS. The results from this research showed that ownership structure partially has negative insignificant effect on corporate financial performance, the capital structure partially has anegative significant effecton corporate financial performance,company sizepartially has positive insignificaneffect on corporate financial performance. Ownership structure, capital strucuture and company size simultaneously has effect on corporate financial performance